BETA-PERIPAPILLARY ATROPHY AND GEOGRAPHIC ATROPHY IN THE COMPARISON OF AGE-RELATED MACULAR DEGENERATION TREATMENTS TRIALS. Issue 1 (January 2021) - Kolomeyer, Anton M.; Smith, Eli; Daniel, Ebenezer; Ying, Gui-Shuang; Pan, Wei; Pistilli, Max; Grunwald, Juan; Maguire, Maureen G.; Kim, Benjamin J.
Abstract : Purpose: To determine associations between beta-peripapillary atrophy (B-PPA) and incidence and growth of geographic atrophy (GA) in eyes treated with anti–vascular endothelial growth factor agents in the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT). Methods: We included 245 cases with incident GA and 245 controls matched by baseline demographics and characteristics associated with development of GA in the CATT. Baseline color images were graded for the type of B-PPA, defined as presence of hypopigmentation with visible choroidal vessels and sclera that is adjacent to the optic disk. Beta-peripapillary atrophy was further classified as scleral ring, sclera, sclera/choroidal blood vessels, or combination. Areas of each type of B-PPA and the circumferential extent of B-PPA were measured. Results: Beta-peripapillary atrophy was present in 58% of eyes developing GA and in 52% without GA ( P = 0.17). The greater circumferential extent of sclera/choroidal blood vessels B-PPA in relation to the optic disk was associated with incident GA ( P = 0.02) and the GA size at first observation ( P = 0.047). Beta-peripapillary atrophy was not associated with GA growth rates ( P >0.05). Patients without B-PPA had a higher number of GA-associated risk alleles of ARMS2 ( P = 0.0003) and HTRA1 ( P = 0.001). Conclusion: The extent of sclera/choroidal blood vessel B-PPA was associated with the GA incidence and size but not with the growth rate in eyes treated for neovascular age-related macular degeneration. Beta-peripapillary atrophy and GA may share some common pathophysiologic pathways unrelated to the GA-associated risk alleles evaluated. Abstract : Supplemental Digital Content is Available in the Text.Our study identified a significant association between the extent of sclera/choroidal blood vessel beta-peripapillary atrophy and incidence and size of geographic atrophy in Comparison of Age-Related Macular Degeneration Treatments Trials. Presence of beta-peripapillary atrophy was also significantly associated with several risk alleles for geographic atrophy.